Effect of foliar application of nitrogen and zinc on the performance of soybean - Rashid, Md Harun; Akther, Shapla; Paul, Swapan Kumar; Afroz, Nisha; Jahan, Israt; Arafat, Yeasin (Fundamental and Applied Agriculture, 2023)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during November 2021 through March 2022 to investigate the effects of foliar application of nitrogen (N) and zinc (Zn) on the performance of Binasoybean-1. The experiment comprised two factors, viz. (A) foliar supplementation of N, and (B) Zn fertilizer management. Factor A had two levels, viz. (i) no N application (control) (N0), and (ii) foliar application of 2% urea solution at pod formation stage (N1). Factor B had four levels, viz. (i) no Zn application (control) (Z0), (ii) basal application recommended dose (RD) of Zn (Z1), (iii) foliar application of 0.5% ZnSO4.7H2O at pod formation stage (Z2), and (iii) basal application of 50% RD of Zn + foliar application of 0.5% ZnSO4.7H2O at pod formation stage (Z3). All growth parameters (leaf area, branch production and plant height), yield contributing characters (total number of pods m−2, number of fertile pods m−2, number of seeds m−2, weight of 1000-seeds), seed yield and stover yield were significantly affected by N fertilization. The highest values were recorded with foliar application of urea (2%) at pod formation stage. Zn management and the interaction of N and Zn management sig- nificantly affected the yield contributing parameters and yields of soybean. However, plant characters were affected neither by Zn nor the interaction. Basal application of 50% RD of Zn + foliar application of 0.5% ZnSO4.7H2O at pod formation stage produced the highest values for all yield contributing characters. Interaction of these N and Zn treatments was also found to be the best combination in terms of these parameters. However, foliar N (2% urea) application coupled with a single foilar spray of 0.5% ZnSO4.7H2O at pod formations stage was as good as the previous combination and produced the statistically similar results in all these yield contributing characters. Therefore, for higher seed yield of soybean, 2% urea solution coupled with a single foilar spray of 0.5% ZnSO4.7H2O at pod formations stage is recommended.